Chalcone-based novel mono and bisthiocarbohydrazone: synthesis, crystal structure, antioxidant property and theoretical evaluation - Lafta, Ahmed Zaki; Kaya, Yeliz; Ercag, Ayse; Zorlu, Yunus; Kaya, Savas; Berisha, Avni (Taylor & Francis Ltd, 2024)
This study describes the synthesis of novel chalconethiocarbohydrazones derived from 2 '-hydroxychalcone and thiocarbohydrazide as potential drugs. The monothiocarbohydrazone (M1) and bisthiocarbohydrazone (M2) compounds were obtained by condensing thiocarbohydrazide with 2 '-hydroxychalcone [1-(2-hydroxyphenyl)-3-phenyl-2-propen-1-one] at 1/1 and 1/2 mol ratios. The synthesized compounds were characterized by elemental analysis, 1H NMR, FT-IR and UV-Vis spectroscopic techniques. The crystal structures of M1 and M2 were solved using single crystal X-ray diffraction method. The total antioxidant capacities of synthesized thiocarbohydrazones were determined by Cupric Reducing Antioxidant Capacity (CUPRAC) method. It was investigated also the radical scavenging activities of these compounds with 2,2-Diphenyl-1-picrylhydrazyl (DPPH) method. When compared to standard compound Trolox, both of the compounds showed good antioxidant activity. For the new compounds, Conceptual Density Functional Theory (CDFT) computations were performed to compute important quantum chemical reactivity descriptors. The chemical reactivities of the studied chemical systems were compared via well-known electronic structure rules of CDFT. Experimentally determined antioxidant activities of the synthesized compounds were supported with Molecular Docking analyses.
Keywords: 2 '-hydroxychalcone; thiocarbohydrazone; synthesis; crystal structure; theoretical calculations